Kontribusi Tarekat Naqsabandiyah Terhadap Pendidikan Agama Islam Dan Perubahan Perilaku Sosial Jamaah (Studi Kasus Jamaah Tarekat Naqsabandiyah Di Dukuh Tompe, Kabupaten Boyolali) - Abdullah, Luqman (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2018)
Luqman Abdullah, The Contribution of Tarekat Naqsabandiyah to Islamic Education and Social Behavior Change. Yogyakarta: Islamic Teaching Department ofTarbiya and Teaching Faculty UIN Sunan Kalijaga Yogyakarta.. This study aims to determine the implementation of the Tarekat Naqsabandiyah in Islamic religious education as well as the contribution of the Tarekat Naqsabandiyah towards Islamic Religious Education and changes in the social behavior of the congregation. The results showed: (1) The form of the Tarekat Naqsabandiyah Education in Tompe Hamlet is applicative yiatu gives a larger portion of the application of education from theoretical education. Coaching is done with Taubat, Suluk, Zuhud and Tawakkal. In addition, in the tarekat education using the approach of remembrance, be it sirr or jahr dhikr. (2) contribution of the Tarekat Naqsabandiyah to Islamic education is: to increase the knowledge of Islam. increase faith in God. , increased charity sholeh. contribution of the Tarekat Naqsabandiyah to social behavior change is: changing anxiety to calm. change the attitude of being rude to be merciful, changing the attitude of dissidents become obedient. change the attitude of shutting open.